Relationship between Physical Activity and Self-esteem of High School Students: Cross-sectional Study - ÖZAYDIN, AYŞE NİLÜFER (My University, 2024)
Objective: This study aimed to investigate the relationship between physical activity and selfesteem of high school students and contribute the literature from a different sociocultural area. Methods: In this descriptive study, whole population of 10th and 11th grade of Capa Science High School (Istanbul/Türkiye) students are invited to study. Voluntarily participating students were asked to answer the questions written on standard survey paper, under the observation of researchers. Survey papers included sociodemographic answers as well as Short Form of International Physical Activity Questionnaire to evaluate physical activity levels and Rosenberg Selfesteem Scale to evaluate self-esteem. IBM SPSS Statistics (Version 11) were used to analyse data. Level of p<0.05 was accepted as statistical significance. Results: Data of 225 persons were succesfully collected (n=278, 80.93%). 16 persons’ data was excluded from physical activity related analyses due to incomplete answers. The 71.60% (n=161) of participants were male, 27.60% (n=62) were female and rest (n=2) did not want to express their genders. Males reported higher self-esteem (p=0.002) and higher physical activity (p=0.031) than females. Self-esteem was associated with regular exercise (p=0.034) status and self-evaluted school success (p=0.001). Self-esteem correlated with participants’ height (p=0.029, r=0.146). Finally, positive correlation between self-esteem and physical activity was found. (p=0.045, r=0.140). Conclusion: Physical activity and self-esteem was correlated with each other in this study. Potential causational relation and underlying mechanisms should be investigated. Keywords: Physical activity, self-esteem, adolescence
Keywords: Tıp; Dahili Tıp Bilimleri; Halk Sağlığı; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Public Health; Health Sciences; Klinik Tıp (MED); Klinik Tıp; SAĞLIK BAKIM BİLİMLERİ VE HİZMETLERİ; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; HEALTH CARE SCIENCES & SERVICES; MEDICINE, GENERAL & INTERNAL; Tıbbi Terminoloji; Tıbbi Sekreterlik ve Transkripsiyon; Sağlık Bilgi Yönetimi; Sağlık Meslekleri (çeşitli); Genel Sağlık Meslekleri; Gözden Geçirme ve Sınav Hazırlığı; Patofizyoloji; Liderlik ve Yönetim; Temel Bilgi ve Beceriler; Toplum Sağlığı ve Evde Bakım; Bakım Planlaması; Değerlendirme ve Teşhis; Dahiliye; Sağlık Politikaları; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Medical Terminology; Medical Assisting and Transcription; Health Information Management; Health Professions (miscellaneous); General Health Professions; Review and Exam Preparation; Pathophysiology; Leadership and Management; Fundamentals and Skills; Community and Home Care; Care Planning; Assessment and Diagnosis; Internal Medicine; Health Policy; Family Practice; Medicine (miscellaneous); General Medicine; Physical activity; self-esteem; adolescence